Interrelationships between social exclusion, mental health and wellbeing in adolescents: insights from a national Youth Survey - K. Filia; S. M. Teo; N. Brennan; T. Freeburn; D. Baker; V. Browne; A. Watson; J. Menssink; A. Prasad; E. Killackey; P. D. McGorry; S. M. Cotton; et al. (Epidemiology and Psychiatric Sciences)
Abstract Aims Adolescence is a critical developmental phase during which young people are vulnerable to the experiences of mental ill-health and social exclusion (consisting of various domains including education and employment, housing, finances and social supports and relationships). The aims of this study were to (i) obtain an understanding of the relationships between social exclusion, mental health and wellbeing of young people; and (ii) identify potentially modifiable targets, or population groups that require greater or targeted supports.